Multiscale Dynamics of Spontaneous Brain Activity Is Associated With Walking Speed in Older Adults. (5th October 2019) - Zhou, Junhong; Poole, Victoria; Wooten, Thomas; Lo, On-Yee; Iloputaife, Ikechukwu; Manor, Brad; Esterman, Michael; Lipsitz, Lewis A
Abstract: Background: In older adults, compromised white matter tract integrity within the brain has been linked to impairments in mobility. We contend that poorer integrity disrupts mobility by altering the processing of sensorimotor and cognitive and attentional resources in neural networks. The richness of information processing in a given network can be quantified by calculating the complexity of resting-state functional MRI time series. We hypothesized that (i) older adults with lower brain complexity, specifically within sensorimotor, executive, and attention networks, would exhibit slower walking speed and greater dual-task costs (ie, dual-task cost) and (ii) such complexity would mediate the effect of white matter integrity on these metrics of mobility. Methods: Fifty-three older adults completed a walking assessment and a neuroimaging protocol. Brain complexity was quantified by calculating the multiscale entropy of the resting-state functional MRI signal within seven previously defined functional networks. The white matter integrity across structures of the corpus callosum was quantified using fractional anisotropy. Results: Participants with lower resting-state complexity within the sensorimotor, executive, and attention networks walked more slowly under single- and dual-task (ie, walking while performing a serial-subtraction task) conditions (β > 0.28, p ≤ .01) and had a greater dual-task cost (β < −0.28, p < .04). Complexity in these networks mediated the influence of the corpus callosum genu on both single- (indirect effects > 0.15, 95% confidence intervals = 0.02–0.32) and dual-task walking speeds (indirect effects > 0.13, 95% confidence intervals = 0.02–0.33). Conclusion: These results suggest that the multiscale dynamics of resting-state brain activity correlate with mobility and mediate the effect of the microstructural integrity in the corpus callosum genu on walking speed in older adults.